Morphology and Distribution of Antennal Sensilla in an Egg Parasitoid Wasp, Anastatus disparis (Hymenoptera: Eupelmidae). Issue 6 (5th December 2022) - Wang, Jianjun; Liu, Pengcheng; Wang, Jianguo; Luan, Qingshu; Jiang, Xu; Cao, Chuanwang
Abstract: The wasp Anastatus disparis is an egg endoparasitoid of a number of Lepidopteran pest species. To better understand the A. disparis olfactory system, we observed the antennal sensilla of males and females under a scanning electron microscope and quantified their sizes and morphological characteristics. We identified the types of sensilla and counted the numbers and locations of the different types on the dorsal and ventral antennal surfaces. The antennae of A. disparis are geniculate, with flagella that comprise 11 subsegments in females and eight in males. The mean antenna length was 1324.10 ± 52.50 μm in females and 1323.93 ± 65.20 μm in males. Ten sensillum types were identified in both sexes: Böhm bristles (BBs), sensilla trichodea (ST, with subtypes STI and STII), sensilla chaetica (SCh), sensilla basiconica (SB, with subtypes SBI and SBII), sensilla placodea (SP), sensilla coeleoconica (SCo), sensilla grooved peg (SGP), sensilla auricillica (SAu), sensilla campaniformia (SCa), and glandular pores (GPs). The total numbers of BBs, STI, SBII, SCa, SCo, and GPs did not differ significantly between the sexes, whereas the total numbers of SCh, SBI, and SAu were significantly greater in females, and those of STII, SP, and SGP were significantly lower. The types, number, and density of antennal sensilla increased from the base to the end. The possible functions of these sensilla in host-detection behavior are discussed.